Employee Turnover and Organizational Performance: a Study of the Brazilian Retail Sector - Luciana Carvalho de Mesquita Ferreira; Ciro Barbosa de Aquino Almeida (BBR: Brazilian Business Review)
This study investigates the relationship between employee turnover and performance in retailing. To achieve this aim, we used data from a single company with several comparable branches and tested whether stores with lower employee turnover have better financial and organizational results (sales and workplace accidents, respectively). This study also analyzes whether Human resources practices, such as rewards, recognition and training, affect employee turnover. The empirical results indicate a strong relationship between employee turnover and sales, supporting results from previous studies. However, the additional relationships were not confirmed. The results do not rule out some hypotheses about the relationship between employee turnover and labor accidents, and further suggest that human resources management practices may increase employee turnover, depending on their motivation and strategic alignment.